Pengaruh Terapi Penggunaan Sarung Tangan Elektrik Menggunakan Alat Pemantau Stroke Berbasis Arduino - Toto Aminoto; mohammad Ali; Ganesa Puput Dinda Kurniawan; Abdurahmah Berbudi BL (Universitas Nurul Jadid, 2026)
Background: Post-stroke rehabilitation is an important process to help patients recover motor function and increase independence in daily activities. One way to recover after a stroke is through the use of electronic gloves. The success of this therapy can be determined by observing finger movement. If the fingers can move, the therapy is considered successful. This movement needs to be monitored using an Arduino-based device to assess its objectivity. Research Objective: To achieve this, it is necessary to develop a device that can monitor the progress of Arduino-based stroke therapy. Methods: The device design includes hardware and software design. The hardware design covers the necessary components, wiring, and device installation. The software design includes a flowchart and software development related to the device's operating principles. Results: An Arduino-based stroke monitoring device has been developed that monitors the development of finger movement resulting from the bending process